Is there ELF in ELT coursebooks? - Vettorel, Paola; Lopriore, Lucilla (Studies in Second Language Learning and Teaching, 2013)
This article aims to explore whether well-attested findings in the fields of World Englishes (WE) and of English as a lingua franca (ELF) have determined a shift in perspective in the overall approach to English language teaching (ELT), and how far this shift has permeated teaching materials and coursebooks. The research study was carried out in Italy, a country where ELT coursebooks have often played a relevant role in introducing innovations in language teaching methodology. The research design included a corpus of ten coursebooks that have been published and adopted in Italian secondary schools in the last 6 years. The coursebooks were evaluated in terms of the presence or absence of references to WE and/or ELF, of awareness-raising activities, of the promotion of using English outside the school environment and of the use of effective English communication and intercultural strategies among nonnative speakers. Findings show that there have been no significant changes in the inclusion of WE- and ELForiented materials and related tasks, apart from the area of promotion of cultural and intercultural awareness.